Property to die for - Mitchell, Christopher ([Australia] : BBC, 2005)
This World reveals a story of life and death on the Moscow property market. Virtually unknown in the West and full of sinister complexities, it's a tale of multi-million dollar scams involving corrupt judges and bureaucrats, bent policemen, fake lawyers, mafia hencmen, and a cast of hapless victims who are either dead or reduced to poverty. Investigating a series of unlawful repossessions that have been ignored by the authorities, property to Die For asks whether Russia is really living up to its claim to be an orderly democratic society, subject to the rule of law
Executif producer, Roger Graef ; editor, Karen O'Connor
Narrator: Paul McGAnn
dvd format
Keywords: Privatization -- Russia (Federation); Russia (Federation) -- Economic policy